Making football safer for women: a systematic review and meta-analysis of injury prevention programmes in 11 773 female football (soccer) players. Issue 18 (6th April 2020) - Crossley, Kay M; Patterson, Brooke E; Culvenor, Adam G; Bruder, Andrea M; Mosler, Andrea B; Mentiplay, Benjamin F
Abstract : Objective: To evaluate the effects of injury prevention programmes on injury incidence in any women's football code; explore relationships between training components and injury risk; and report injury incidence for women's football. Design: Systematic review and meta-analysis. Data sources: Nine databases searched in August 2019. Eligibility criteria: Randomised controlled trials evaluating any injury prevention programme (eg, exercise, education, braces) were included. Study inclusion criteria were: ≥20 female football players in each study arm (any age, football code or participation level) and injury incidence reporting. Results: Twelve studies, all in soccer, met inclusion criteria, with nine involving adolescent teams (aged <18 years). All studies (except one) had a high risk of bias. Eleven studies examined exercise-based programmes, with most (9/11) including multiple (≥2) training components (eg, strength, plyometric, balance exercises). Multicomponent exercise programmes reduced overall (any reported) injuries (incidence rate ratio (IRR) 0.73, 95% CI 0.59 to 0.91) and ACL injuries (IRR 0.55, 95% CI 0.32 to 0.92). For exercise-based strategies (single-component and multicomponent), hamstring injuries were also reduced (IRR 0.40, 95% CI 0.17 to 0.95). While exercise-based strategies resulted in less knee, ankle and hip/groin injuries, and the use of multiple training components was associated with greater reductions in overall and knee injuries, further studies would be required to increase the precision of these results. The incidence of overall injuries in women's football was 3.4 per 1000 exposure hours; with ankle injuries most common. Conclusion: In women's football, there is low-level evidence that multicomponent, exercise-based programmes reduce overall and ACL injuries by 27% and 45%, respectively. PROSPERO registration number: CRD42018093527.